3D optical spectroscopic study of NGC 3344 with SITELLE: I. Identification and confirmation of supernova remnants. Issue 1 (25th June 2019) - Moumen, I; Robert, C; Devost, D; Martin, R P; Rousseau-Nepton, L; Drissen, L; Martin, T
ABSTRACT: We present the first optical identification and confirmation of a sample of supernova remnants (SNRs) in the nearby galaxy NGC 3344. Using high spectral and spatial resolution data, obtained with the CFHT imaging Fourier transform spectrograph SITELLE, we identified about 2200 emission line regions, many of which are H ii regions, diffuse ionized gas regions, and also SNRs. Considering the stellar population and diffuse ionized gas background, which are quite important in NGC 3344, we have selected 129 SNR candidates based on four criteria for regions where the emission lines flux ratio [S ii ]/H α ≥ 0.4. Emission lines of [O ii ] λ3727, H β, [O iii ] λλ4959, 5007, H α, [N ii ] λλ6548, 6583, and [S ii ] λλ6716, 6731 have been measured to study the ionized gas properties of the SNR candidates. We adopted a self-consistent spectroscopic analysis, based on Sabbadin plots and Baldwin, Phillips & Terlevich diagrams, to confirm the shock-heated nature of the ionization mechanism in the candidates sample. With this analysis, we end up with 42 Confirmed SNRs, 45 Probable SNRs, and 42 Less likely SNRs. Using shock models, the confirmed SNRs seem to have a metallicity ranging between Large Magellanic Cloud and 2×solar. We looked for correlations between the size of the confirmed SNRs and their emission lines ratios, their galaxy environment, and their galactocentric distance: We see a trend for a metallicity gradient among the SNR population, along with some evolutionary effects.